DISPUTE RESOLUTION RELATED TO THE DETERMINATION OF COMPENSATION PRICE IN LAND ACQUISITION FOR PUBLIC INTEREST OF WONOKROMO - JOMBANG DOUBLE TRACK RAILWAY - Elvira, Anita Jihan; Yahman, Dr. (jfpublisher, 2023)
Land acquisition for development in the public interest is an act of acquiring land by providing compensation to the party releasing the land. This provision is regulated in Law No. 2/2012 on Land Acquisition for Development in the Public Interest. However, in practice, land acquisition activities often trigger conflicts regarding the provision of compensation. These conflicts often arise from disagreements that arise in providing the value of compensation provided by the appraisal team, as well as because the party releasing the land considers that the nominal compensation given is different from the value of the land. This research aims to examine the conflicts in land acquisition to identify the legal provisions used when granting compensation and the settlement of disputes over compensation in land acquisition to answer the problems that arise in every practice of land acquisition for the public interest. The method used in this research is juridical empirical based on field facts. The research findings revealed that the provision of compensation is not given based on the selling value of the tax object (NJOP), which is even below the market price. Therefore, it is necessary to review the legal rules in providing compensation for land acquisition, considering the importance of the existence of land for the public interest in ensuring the sustainability of human life.